Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Let $X_0,X_1,X_2,...$ be independent random variables with $$P(X_n =1)=P(X_n =-1)={1\over 2},\forall n$$ Let $$Z_n = \prod_{i=0}^n X_i .$$

Show that $Z_1,Z_2,...$ are independent.

An intuition is to prove it by induction. By definition a sequence of r.v.s $(X_n)_{n\ge1}$ are independent if the sigma algebra generated by them are independent. Here, I try to prove $P(Z_1=1,Z_2=-1)=P(Z_1 =1)P(Z_2 =-1)$ and this is easy to do, but when includes like n R.V.s should I write all the possible combination of events? I am not so sure how to write this proof.

share|cite|improve this question
This will help you , I think… – Airbag Jan 11 '14 at 12:30

For any finite $S\subset\left\{ 0,1,2,\ldots\right\} $ define $Z_{S}:=\prod_{s\in S}X_{s}$. Note that here $Z_{n}$ and $Z_{\left\{ 0,\ldots,n\right\} }$ denote the same random variable.

By induction it can be shown that $Z_{n}$ has exactly the same distribution as - let's pick one out - $X_{0}$ . It uses the apparant independency of $Z_{n-1}$ and $X_{n}$. Note that $Z_{n}$ can only take values in $\left\{ -1,1\right\} $ so that it is enough to prove that $P\left\{ Z_{n}=1\right\} =\dfrac{1}{2}$.

$P\left\{ Z_{n}=1\right\} =P\left\{ Z_{n-1}=1\wedge X_{n}=1\right\} +P\left\{ Z_{n-1}=-1\wedge X_{n}=-1\right\} =P\left\{ Z_{n-1}=1\right\} P\left\{ X_{n}=1\right\} +P\left\{ Z_{n-1}=-1\right\} P\left\{ X_{n}=-1\right\} =\dfrac{1}{2}\times\dfrac{1}{2}+\dfrac{1}{2}\times\dfrac{1}{2}=\dfrac{1}{2}$.

In fact this means that $Z_{S}$ has the same distribution as $X_{0}$ for any finite $S\subset\left\{ 0,1,2,\ldots\right\} $.

Let $n,k$ be integers with $k>0$ and let $S:=\left\{ n+1,\cdots,n+k\right\} $. Then $Z_{n}$ and $Z_{S}$ are independent and for $\varepsilon,\delta\in\left\{ -1,1\right\} $ we find:

$P\left\{ Z_{n}=\varepsilon\wedge Z_{n+k}=\delta\right\} =P\left\{ Z_{n}=\varepsilon\wedge Z_{S}=\delta\varepsilon^{-1}\right\} =P\left\{ Z_{n}=\varepsilon\right\} P\left\{ Z_{S}=\delta\varepsilon^{-1}\right\} =\dfrac{1}{2}\times\dfrac{1}{2}=P\left\{ Z_{n}=\varepsilon\right\} P\left\{ Z_{n+k}=\delta\right\} $.

This proves that $Z_n$ and $Z_{n+k}$ are independent.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.